Supply chain design to support cross-border e-commerce remove - Lim, Sherilyn Su Ying (2016)
The online market has proven to be a dynamic, fast-growing market place in the recent years. With the likes of Amazon, Alibaba, E-bay and Groupon, cross borders expansion has yielded an active contribution towards E-commerce’s steady growing statistical figures. The two basic mechanism of direct E-commerce purchase are from the merchant’s website browser or application (app). With this ease of convenience, E-commerce companies and freight forwarders have anticipated a perpetual increase in demands of customer service, extending from the start of the purchase till the customer receives the products, independent of their location on the world map. Several crucial gaps regarding both existing or new start-up E-commerce companies’ involvement across borders remains unanswered. It becomes vital to have an effective management of E-commerce transactions in international supply chain. As such, this study specifically looks into this issue that can impede the economy’s future growth and consider how various factors differs. The aim is to offer a strategic supply chain design framework of a suitable roadmap for companies to make their entrance into international country and facilitate a smooth launch of cooperation between suppliers, service providers and customers across borders. This study will examine how the proposed supply chain designs can produce significant improvement in distribution network performances and build sustainable growth into E-commerce on a global scale. Through a detailed case study method, Alibaba’s Taobao distribution network will be branched into three possible roadmaps. With a clearer strategic view, companies can get closer to achieving their target with their identified key parameters or tradeoffs.